NATURAL ICE MOUNDS OF THE MIDDLE AND SOUTHERN SAKHALIN MUDFLOW BASINS - Svetlana V. Rybalchenko; Konstantin V. Verkhovov (Водное хозяйство России: проблемы, технологии, управление)
The article deals with the ice mounds formation processes in the mudflow basins. Small natural frosts are widespread on the territory of Middle and Southern Sakhalin within the slope and small valley debris flow basins, along with dangerous slope exogenous processes (debris flows, landslides, erosion, etc.), often having a paragenetic nature of the current. The mechanism of ice data formation is due to the hydro/meteorological features of the territory, as well as disturbance of the thermal, hydrological or hydrogeological regime of the debris flow basin. The main reason for the formation of natural ice mounds in the valley debris flow basins is disturbance of the hydrological regime of the catchment basin during debris flow formation, which mainly contributes to the annual solid runoff of first order watercourses. Scum of slope debris flow basins are formed in case of violation of the thermal regime of the surface and soil of the debris flow basin due to climatic anomalies, as well as damage to natural heat-insulating coverings: snow and soil-vegetable. It is also possible to form sloping ice as a result of a violation of the hydrogeological regime of the catchment basin under anthropogenic impact or the development of dangerous exogenous slope processes with a sufficient depth of rock capture. Cryogenic processes of ice formation affect debris flow and channel processes.